TANDA VERBAL PADA FILM ANIMASI “El Empleo” - Nyoman Miyarta Yasa; Hasbullah Hasbullah (Jurnal Nawala Visual, 2020)
"El Empleo" is a silent animated film that won 102 Awards. This animated film is only equipped with sound effects, so that makes it alive. This film is very important to be investigated when viewed from the uniqueness that is located in a strange visual, humans are used as tools and objects around their residence. This animated film, communicates messages through verbal signs However, not everyone understands the meaning of the sign. Therefore, the problem that arises in this research is about how the verbal signs are displayed in the animated film " El Empleo ". The purpose of this study is to analyze in-depth in the first, middle and end scenes of verbal signs, the intent that the animator communicates in the animated film. The method used is qualitative interpretative with the foundation of Charles S. Pierce's semiotics theory. The results of this study are verbal signs in the form of icons of men living as bosses; human symbolized as a seat, vehicle (taxi), traffic signs, and as a toilet mat; index contained in the expression of the face of the character/character that indicates power and oppression. In conclusion, at the level of verbal signs in the first, middle, and final scenes, they can be divided into icons depicting a man living a boss; humans as subordinates are symbolized as seats, vehicles, traffic signs, even as footwear in front of the toilet door, the index looks at the boss's facial expression, and subordinates that indicate oppression. The purpose and objectives as a symbolic message that signifies power are not always owned, but on the contrary the power will be oppressed.